Using computer vision for equitable property valuation in urban areas (Research, Society and Development, 2025)
The objective of this article is to present a study on the use of computer vision based on AI (Artificial Intelligence) for equitable property valuation in urban areas. This systematic literature review explores the emerging field of applying Artificial Intelligence, particularly computer vision, to improve equity, accuracy, and efficiency in property valuation in urban environments. Drawing on a wide range of academic papers—including discussions on AI in smart cities, computer vision applications, and systematic review methodologies—this study summarizes the current knowledge on the potential of AI-driven computer vision to overcome the limitations of conventional methods and contribute to more equitable urban development.